Marine heatwave impacts on newly-hatched planktonic larvae of an estuarine crab - Marochi, Murilo Zanetti [UNESP]; De Grande, Fernando Rafael [UNESP]; Farias Pardo, Juan Carlos; Montenegro, Álvaro; Costa, Tânia Marcia [UNESP] (Elsevier, 2022)
Climate change is imposing constant and more severe environmental challenges to coastal and marine species. Regional climate and species acclimation capacity determine the communities' ecological response to stressors. Marine heatwave events are of serious threat to species fitness and survivorship, even more to the sensitive early-history stages of ectotherms. By combining modeled regional historical data and climate change predictions with manipulative experiments, we evaluated the potential impact of marine heatwaves in a widespread and abundant planktonic larvae of the fiddler crab Leptuca thayeri. Larvae survival was affected by temperature increase with lowest survival probability under higher temperature treatments regardless of pH conditions. Larval physiology was affected by both temperature increase and pH conditions. With heatwaves becoming more frequent, hotter, and lasting longer in the region, we could expect potential reductions in the larval recruitment and stocks with cascade ecological negative effects on estuarine habitats.
Keywords: Climate change; Early-life stages; Ectotherms; Thermal Stress